2015
DOI: 10.4049/jimmunol.1500197
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia/Reoxygenation Inhibits P2Y11 Receptor Expression and Its Immunosuppressive Activity in Human Dendritic Cells

Abstract: High concentrations of extracellular ATP (eATP) resulting from cell damage may be found during an ischemia/reperfusion (I/R) episode at the site of injury. eATP activates purinergic receptors in dendritic cells (DCs) and may inhibit inflammation. This immunosuppressive activity could be of interest in the field of I/R, which is an inflammatory condition involved in myocardial infarction, stroke, and solid organ transplantation. However, the specific purinergic receptor responsible for this effect remains to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 57 publications
2
28
0
Order By: Relevance
“…The endocannabinoid system including CB2 in DCs is involved in the suppression of inflammatory response 34 . It has also been reported that, upon activation by ATP, P2Y11 suppresses the inflammatory response in DCs 35,36 . Extracellular ATP induces DCs to differentiate into an anti-inflammatory type and suppresses the secretion of pro-inflammatory cytokines, including IL-12p70 and IL-6 via P2Y11; 36 in addition, NF546, a P2Y11-selective agonist, suppresses IL-12p70 production 35 .…”
Section: Discussionmentioning
confidence: 91%
“…The endocannabinoid system including CB2 in DCs is involved in the suppression of inflammatory response 34 . It has also been reported that, upon activation by ATP, P2Y11 suppresses the inflammatory response in DCs 35,36 . Extracellular ATP induces DCs to differentiate into an anti-inflammatory type and suppresses the secretion of pro-inflammatory cytokines, including IL-12p70 and IL-6 via P2Y11; 36 in addition, NF546, a P2Y11-selective agonist, suppresses IL-12p70 production 35 .…”
Section: Discussionmentioning
confidence: 91%
“…Studies of microarray analysis of ATP‐stimulated human DCs have revealed induction of thrombospondin 1 and indoleamine 2.3‐dioxygenase (IDO), two immunosuppressive genes, suggesting an important role for ATP in promoting immunotolerance . This specific role of eATP in favoring immunotolerance by conferring immunosuppressive properties to DCs has been also supported by data showing no impacts of ATP on IL‐10 but rather selectively dampening pro‐inflammatory cytokine secretion . In the context of TME, recent studies have proposed a role for eATP in the activation of the NLRP3 inflammasome in DCs through P2X7R …”
Section: Myeloid Cellsmentioning
confidence: 92%
“…Along these lines, ATP appears to be implicated in activation of the NLRP3 inflammasome (212,257,393,560,632,668). Interestingly, a recent study on the hypoxia/ reoxygenation model found that eATP was able to induce maturation of human monocyte-derived DCs (74).…”
Section: Class II Dampsmentioning
confidence: 99%